Halogen-doped quaternary positive electrode material and preparation method and application thereof

Through step-by-step mixing and multi-step heat treatment, halogen-doped quaternary cathode material was prepared, solving the thermal stability and capacity retention problems of quaternary lithium batteries under high nickel content, and achieving better electrochemical performance and rate performance.

CN119905499AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311415492.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The thermal stability and capacity retention rate of existing quaternary lithium batteries decrease after the nickel content exceeds 90%, and there are technical difficulties in uniform dispersion of aluminum elements in NCMA batteries. Halogen doping is mainly aimed at the surface doping of ternary materials, and there are few reports of bulk-phase doping of quaternary materials.

Method used

The halogen-doped quaternary positive electrode material is prepared by controlling the mixing and heat treatment sequence of each metal source and introducing halogen through metal halides to ensure that the elements are uniformly distributed and the halogen enters the body phase and lattice of the material.

Benefits of technology

提高了材料结构稳定性和电化学循环性能,增大了晶胞参数,促进锂离子的传输,从而提升倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905499A_ABST
    Figure CN119905499A_ABST
Patent Text Reader

Abstract

The invention relates to a halogen-doped quaternary positive electrode material and a preparation method and application thereof, and the method comprises the following steps: S1, carrying out first solid phase mixing on nickel hydroxide, an aluminum source and a manganese source to obtain a first solid material; s2, carrying out second solid phase mixing on the first solid material and a cobalt source, and carrying out first heat treatment on the obtained mixed material in a first oxygen-containing atmosphere to obtain a second solid material; s3, carrying out third solid phase mixing on the second solid material and a lithium source, and carrying out second heat treatment on the obtained mixed material in a second oxygen-containing atmosphere; at least one of the cobalt source, the manganese source and the aluminum source contains halogen; the method disclosed by the invention is simple in steps, elements in the prepared halogen-doped quaternary material are uniformly distributed, the halogen elements can achieve a uniform bulk phase doping effect, and the halogen-doped quaternary material has relatively high electrochemical cycle performance and rate capability when being used as a battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of preparation of quaternary materials for lithium-ion batteries, and in particular, to a halogen-doped quaternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Increasing the proportion of nickel in ternary lithium batteries can increase the energy density of the battery. However, after the nickel content exceeds 90% (that is, ultra-high nickel batteries), the thermal stability of the battery will decrease rapidly, and the capacity retention rate will also begin to decrease. That is, safety is reduced and it is more prone to decay. The NCMA battery, on the other hand, is based on the NCM ultra-high nickel battery with 1% aluminum added. Studies have shown that compared to NCA materials, the battery performance of NCMA has been greatly improved. However, there are still certain technical difficulties in achieving uniform dispersion of aluminum elements.

[0003] In addition, bulk ion doping can further stabilize the layered structure and reduce the degree of cation mixing, thereby improving the structural stability of high-nickel materials. Studies have shown that halogen atom doping can partially replace O 2- , changing the valence state of transition metal ions, thereby changing the lattice structure parameters, and also having a certain impact on its electrochemical performance. However, at present, halogen doping is mainly for the surface doping of ternary materials, while halogen doping for bulk doping and quaternary materials is rarely reported. Summary of the invention

[0004] The purpose of the present disclosure is to provide a halogen-doped quaternary positive electrode material and a preparation method and application thereof.

[0005] In order to achieve the above object, the present disclosure provides a method for preparing a halogen-doped quaternary positive electrode material in a first aspect, the method comprising the following steps:

[0006] S1, performing a first solid phase mixing of nickel hydroxide, an aluminum source and a manganese source to obtain a first solid material;

[0007] S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;

[0008] S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere;

[0009] At least one of the cobalt source, the manganese source, and the aluminum source contains a halogen.

[0010] Optionally, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide;

[0011] The manganese source includes one or more of manganese hydroxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate, manganese acetate, manganese fluoride, manganese chloride, manganese bromide, and manganese iodide;

[0012] The cobalt source includes one or several of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide, and cobalt iodide;

[0013] The lithium source includes one or several of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0014] Optionally, the methods of the first solid-phase mixing, the second solid-phase mixing, and the third solid-phase mixing include solid-phase ball milling, and the times are 1-5 h respectively.

[0015] Optionally, in step S2, the method of the first heat treatment includes roasting, and the conditions of the first heat treatment include: the time is 2-8 h, and the temperature is 400-900 °C.

[0016] Optionally, in step S3, the method of the second heat treatment includes roasting, and the conditions of the second heat treatment include: the time is 10-20 h, and the temperature is 600-850 °C.

[0017] Optionally, the average particle size of the nickel hydroxide is 5-15 μm.

[0018] Optionally, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere.

[0019] The second aspect of the present disclosure provides a halogen-doped quaternary cathode material prepared by using the method described in the first aspect of the present disclosure.

[0020] The third aspect of the present disclosure provides a halogen-doped quaternary cathode material, and the chemical formula of the quaternary cathode material is LiNi 1-x-y-z Co x Mn y Al z O 2-0.5p X p , 0.6 ≤ 1 - x - y - z < 1, 0 < x ≤ 0.15, 0 < y ≤ 0.15, 0 < z ≤ 0.1, 0 < p ≤ 0.1, and X is one or more of F, Cl, Br, and I.

[0021] The fourth aspect of the present disclosure provides a lithium-ion battery, which includes a cathode, an electrolyte, and an anode, and the cathode includes the halogen-doped quaternary cathode material described in the second aspect or the third aspect of the present disclosure.

[0022] Through the above technical scheme, the present invention adopts a method of step-by-step mixing combined with multi-step heat treatment, controls the order of mixing and heat treatment of each metal source, and introduces halogens through metal halides to obtain a halogen-doped quaternary positive electrode material, in which the elements are evenly distributed, and at least part of the halogen elements can be doped into the bulk phase of the material and enter the interior of the crystal lattice, which can not only increase the structural stability of the material and improve the electrochemical cycle performance; but also increase the unit cell parameters and promote the transmission of lithium ions, thereby improving its rate performance.

[0023] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0025] Figure 1 The electrochemical rate curves of the quaternary positive electrode materials A1, A2, D1 and D2 prepared in Examples 1-2 and Comparative Examples 1-2 of the present application.

[0026] Figure 2 Electrochemical cycle curves of quaternary positive electrode materials A1, A2, D1 and D2 prepared in Examples 1-2 and Comparative Examples 1-2 of the present application and a capacity retention rate graph after 150 cycles.

[0027] Figure 3 X-ray diffraction patterns of quaternary positive electrode materials A1, A2, D1 and D2 prepared in Examples 1-2 and Comparative Examples 1-2 of the present application.

[0028] Figure 4 Scanning electron microscope and element distribution diagram of the Cl-doped quaternary positive electrode material A1 prepared in Example 1 of the present application.

[0029] Figure 5 Scanning electron microscope and element distribution diagram of the Cl-doped quaternary positive electrode material D2 prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0030] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0031] The first aspect of the present disclosure provides a method for preparing a halogen-doped quaternary positive electrode material, the method comprising the following steps:

[0032] S1, performing a first solid phase mixing of nickel hydroxide, an aluminum source and a manganese source to obtain a first solid material;

[0033] S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;

[0034] S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere;

[0035] At least one of the cobalt source, the manganese source, and the aluminum source contains a halogen.

[0036] The present invention adopts a method of step-by-step mixing combined with multi-step heat treatment, controls the order of mixing and heat treatment of each metal source, and introduces halogen through metal halide to prepare a halogen-doped quaternary material, in which each element is mixed relatively uniformly, and at least part of the halogen can be doped into the bulk phase of the material and enter the interior of the lattice; it is used as a positive electrode material for a lithium-ion battery, and has good cycle performance and rate performance.

[0037] In the present disclosure, "at least one of the cobalt source, the manganese source and the aluminum source contains halogen" means that one, two or three of the cobalt source, the manganese source and the aluminum source contain halogen; the halogen may be one or more of fluorine, chlorine, bromine and iodine.

[0038] According to one embodiment of the present disclosure, the nickel hydroxide has a spherical and / or quasi-spherical morphology, and the spherical and quasi-spherical shapes are both conventionally defined in the art. Preferably, the average particle size of the nickel hydroxide is 5-15 μm.

[0039] According to one embodiment of the present disclosure, in order to achieve uniform mixing, the first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling for 1-5 hours, preferably 2-4 hours; solid phase ball milling can be performed on a planetary ball mill, for example.

[0040] According to one embodiment of the present disclosure, the types of manganese source, aluminum source, cobalt source and lithium source are conventional in the art. For example, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide. When the aluminum source includes more than two substances, the proportion thereof is not specifically limited; the cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide. When the cobalt source includes more than two substances, the proportion thereof is not specifically limited; the manganese source includes one or more of manganese hydroxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate, manganese acetate, manganese fluoride, manganese chloride, manganese bromide and manganese iodide. When the manganese source includes more than two substances, the proportion thereof is not specifically limited; the lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate. When the lithium source includes more than two substances, the proportion thereof is not specifically limited.

[0041] In the present disclosure, the lithium source does not contain halogen.

[0042] According to an embodiment of the present disclosure, in step S2, the first heat treatment method includes roasting, and the conditions of the first heat treatment include: time is 2-8h, temperature is 400-900℃; preferably, time is 3-7h, temperature is 500-800℃; this condition can exert the migration effect of metal ions and promote uniform mixing of various elements.

[0043] According to an embodiment of the present disclosure, in step S3, the second heat treatment method includes roasting, and the conditions of the second heat treatment include: time is 10-20h, temperature is 600-850°C; preferably, time is 12-18h, temperature is 700-800°C; under this condition, the diffusion of Li is better, and a higher material capacity is obtained.

[0044] According to one embodiment of the present disclosure, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere, wherein the definitions of the oxygen-containing atmosphere and the air atmosphere are conventional in the art.

[0045] In the present disclosure, the calcination method is conventional in the art, for example, it can be carried out in a sagger.

[0046] In the present disclosure, part of the halogen may be lost during the preparation process.

[0047] In the present disclosure, the amounts of nickel hydroxide, manganese source, cobalt source and aluminum source are set according to the molar ratio of nickel element, cobalt element and aluminum element in the product.

[0048] According to an embodiment of the present disclosure, the molar ratio of the lithium source in terms of lithium element to the second solid material in terms of the total amount of manganese element, nickel element, cobalt element, and aluminum element can be, for example, (0.8 - 1.2):1, preferably (0.95 - 1.15):1, and part of the lithium source is lost during ball milling and heat treatment.

[0049] The second aspect of the present disclosure provides a halogen-doped quaternary cathode material prepared by the method described in the first aspect of the present disclosure.

[0050] The third aspect of the present disclosure provides a halogen-doped quaternary cathode material, and the quaternary cathode material includes particles with the chemical formula LiNi 1-x-y-z Co x Mn y Al z O 2-0.5p X p where 0.6 ≤ 1 - x - y - z < 1, 0 < x ≤ 0.15, 0 < y ≤ 0.15, 0 < z ≤ 0.1, 0 < p ≤ 0.1, and X is one or more of F, Cl, Br, and I.

[0051] According to an embodiment of the present disclosure, 0.8 ≤ 1 - x - y - z ≤ 0.96, 0.02 ≤ x ≤ 0.10, 0.02 ≤ y ≤ 0.1, 0 < z ≤ 0.05.

[0052] The halogen-doped quaternary cathode material described in the second aspect of the present disclosure has the same characteristics as the quaternary cathode material described in the third aspect of the present disclosure, and will not be elaborated here.

[0053] The fourth aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode, an electrolyte, and a negative electrode, and the positive electrode includes the halogen-doped quaternary cathode material described in the second aspect or the third aspect of the present disclosure.

[0054] According to an embodiment of the present disclosure, the negative electrode is conventional in the art, and can include, for example, one or several of lithium sheets, carbon materials, and silicon-carbon composite materials.

[0055] According to an embodiment of the present disclosure, the electrolyte is conventional in the art, and can include, for example, one or several of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, lithium hexafluorophosphate, and dimethyl carbonate.

[0056] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form.

[0057] The raw materials used in the examples are all obtained through commercial channels and are all of analytical purity unless otherwise specified.

[0058] The testing instrument model of the scanning electron microscope SEM is FEIQUANTA400, and the method is that the acceleration voltage is 20 kV;

[0059] The X-ray diffraction pattern XRD test instrument model is the X-ray powder diffractometer of Philips Company of the United States. The method is to use Cu target anode Kα radiation source, step width of 0.02°, scanning speed of 2° / min, 2θ=10°-80°.

[0060] The testing instrument model of X-ray photoelectron spectroscopy XPS is ESCALAB 250.

[0061] Testing method for the chemical formula of positive electrode materials: Inductively coupled plasma mass spectrometry.

[0062] Example 1

[0063] The chlorine-doped quaternary cathode material A1 was prepared by the following steps:

[0064] (1) according to the molar ratio of n(Ni):n(Al):n(Mn)=0.89:0.01:0.05, 0.89 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.01 mol of aluminum chloride and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0065] (2) according to the molar ratio of n(Ni):n(Co)=0.89:0.05, 0.05 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;

[0066] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain a chlorine-doped quaternary positive electrode material A1 with a chemical formula of LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O 1.992 Cl 0.016 , the parameters are listed in Table 1.

[0067] Example 2

[0068] The chlorine-doped quaternary cathode material A2 was prepared by the following steps:

[0069] (1) According to the molar ratio of n(Ni):n(Al):n(Mn)=0.89:0.01:0.05, 0.89 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.01 mol of aluminum hydroxide and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0070] (2) according to the molar ratio of n(Ni):n(Co)=0.89:0.05, 0.035 mol of cobalt acetate and 0.015 mol of cobalt chloride were weighed and added to the first solid material, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 h to obtain a second solid material;

[0071] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain a chlorine-doped quaternary positive electrode material A2 with a chemical formula of LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O 1.992 Cl 0.016 , the parameters are listed in Table 1.

[0072] Example 3

[0073] The fluorine-doped quaternary cathode material A3 was prepared by the following steps:

[0074] (1) According to the molar ratio of n(Ni):n(Al):n(Mn)=0.92:0.02:0.02, 0.92 mol of spherical nickel hydroxide (average particle size of 8.8 μm), 0.02 mol of aluminum hydroxide powder and 0.02 mol of manganese carbonate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0075] (2) According to the molar ratio of n(Ni):n(Co)=0.92:0.04, 0.025 mol of cobalt acetate and 0.015 mol of cobalt fluoride were weighed and added to the first solid material, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 600° C. for 6 h to obtain a second solid material;

[0076] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.06:1, 1.06 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 3 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 710°C for 18 h. The obtained solid product was crushed and sieved to obtain a fluorine-doped quaternary positive electrode material A3 with a chemical formula of LiNi 0.92 Co 0.04 Mn 0.02 Al 0.02 O 1.9895 F 0.021 .

[0077] Example 4

[0078] The bromine-doped quaternary cathode material A4 was prepared by the following steps:

[0079] (1) according to the molar ratio of n(Ni):n(Al):n(Mn)=0.83:0.02:0.05, 0.83 mol of spherical nickel hydroxide (average particle size of 8.2 μm), 0.02 mol of aluminum hydroxide and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0080] (2) according to the molar ratio of n(Ni):n(Co)=0.83:0.10, 0.08 mol of cobalt carbonate and 0.02 mol of cobalt bromide were weighed and added to the first solid material, mixed on a planetary ball mill for 3 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;

[0081] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.06:1, 1.06 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 3 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 700°C for 18 h. The obtained solid product was crushed and sieved to obtain a bromine-doped quaternary positive electrode material A4 with a chemical formula of LiNi 0.83 Co 0.1 Mn 0.05 Al 0.02 O 1.9951 Br 0.0098 .

[0082] Example 5

[0083] The iodine-doped quaternary cathode material A5 was prepared by the following steps:

[0084] (1) According to the molar ratio of n(Ni):n(Al):n(Mn)=0.85:0.02:0.05, 0.85 mol of spherical nickel hydroxide (average particle size of 8.2 μm), 0.01 mol of aluminum hydroxide, 0.01 mol of aluminum iodide and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 3 hours on a planetary ball mill to obtain a first solid material;

[0085] (2) according to the molar ratio of n(Ni):n(Co)=0.85:0.08, 0.08 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 3 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 800° C. for 6 hours to obtain a second solid material;

[0086] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.08:1, 1.08 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 3 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 720°C for 18 h. The obtained solid product was crushed and sieved to obtain an iodine-doped quaternary positive electrode material A5 with a chemical formula of LiNi 0.85 Co 0.08 Mn 0.05 Al 0.02 O 1.994 I 0.012 .

[0087] Comparative Example 1

[0088] The quaternary cathode material D1 was prepared by the following steps:

[0089] (1) According to the molar ratio of n(Ni):n(Al):n(Mn)=0.89:0.01:0.05, 0.89 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.01 mol of aluminum hydroxide and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0090] (2) according to the molar ratio of n(Ni):n(Co)=0.89:0.05, 0.05 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;

[0091] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.05:1, 1.05 mol of lithium hydroxide and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain a quaternary positive electrode material D1 with a chemical formula of LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O2, parameters are listed in Table 1.

[0092] Comparative Example 2

[0093] The chlorine-doped quaternary cathode material D2 was prepared by the following steps:

[0094] (1) According to the molar ratio of n(Ni):n(Al):n(Mn)=0.89:0.01:0.05, 0.89 mol of spherical nickel hydroxide (average particle size of 8.5 μm), 0.01 mol of aluminum hydroxide and 0.05 mol of manganese oxalate were weighed respectively, and mixed for 2 hours on a planetary ball mill to obtain a first solid material;

[0095] (2) according to the molar ratio of n(Ni):n(Co)=0.89:0.05, 0.05 mol of cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment under an oxygen atmosphere at a temperature of 700° C. for 5 hours to obtain a second solid material;

[0096] (3) According to the molar ratio of n(Li):n(Ni+Co+Mn+Al)=1.05:1, 1.02 mol of lithium hydroxide, 0.03 mol of lithium chloride and 1 mol of the second solid material were weighed respectively, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a second heat treatment under an oxygen atmosphere at a temperature of 730°C for 15 h. The obtained solid product was crushed and sieved to obtain a chlorine-doped quaternary positive electrode material D2 with a chemical formula of LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O 1.991 Cl 0.018 , the parameters are listed in Table 1.

[0097] Table 1

[0098] Material No. Unit cell parameter c(nm) Atomic ratio of surface Cl element (%) Example 1 A1 1.42467 0.18 Example 2 A2 1.42464 0.12 Comparative Example 1 D1 1.42275 0 Comparative Example 2 D2 1.42371 0.58

[0099] The unit cell parameters in Table 1 were tested by XRD, and the “atomic ratio of surface Cl element” refers to the ratio of Cl atoms on the particle surface to all atoms on the surface, which was tested by XPS.

[0100] According to the data in Table 1, compared with D1-D2, the unit cell parameters of the halogen-doped quaternary positive electrode materials A1 and A2 prepared by the method disclosed in the present invention are larger, which is conducive to the transmission of lithium ions; when the Cl dosage is the same, the atomic content of the surface Cl element of A1 and A2 is relatively low, indicating that the halogen is doped into the interior of the material.

[0101] XRD tests were performed on A1, A2, D1 and D2, and the results are as follows: Figure 3 shown.

[0102] according to Figure 3 It can be seen that compared with the quaternary positive electrode material D1 without halogen doping, the peak positions of halogen-doped A1, A2 and D2 are shifted. When the Cl dosage is the same, the peak positions of A1 and A2 are shifted to a greater extent relative to the surface halogen-doped material D2, indicating that the doping degree of Cl element is relatively high and at least part of the halogen is doped into the crystal lattice of the material.

[0103] The scanning electron microscope (SEM) test was performed on samples A1 and D2 to analyze the element distribution of the samples. The results are as follows: Figure 4 and Figure 5 shown.

[0104] according to Figure 4 and Figure 5 It can be seen that compared with D2, the Ni, Co, Mn, Al, and Cl elements in A1 are evenly dispersed, indicating that the elements in the halogen-doped quaternary positive electrode material prepared by the method disclosed in the present invention are evenly distributed.

[0105] Test Case

[0106] The electrochemical performance of the quaternary materials A1, A2, D1 and D2 prepared in the examples and comparative examples was tested, and the specific steps were as follows:

[0107] The positive electrode material, conductive agent (acetylene black), and binder (polyvinylidene fluoride) were weighed in a mass ratio of 8:1:1 and mixed evenly with the solvent (N-methylpyrrolidone), coated on aluminum foil and cut into sheets as the positive electrode; then mixed with lithium sheet, electrolyte (1 mol·L -1 LiPF6 ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate solution, mass ratio of 1:1:1) and a separator (Celgard2300) were used to form a lithium ion half-cell, and the electrochemical performance test results are as follows Figure 1 and 2 shown.

[0108] Specific test conditions: the charge and discharge voltage range is 2.75-4.3V; the charge and discharge rate is 0.1C for the first 4 times and 0.5C after the 5th time; the test temperature is 35℃.

[0109] according to Figure 1 It can be seen that under 10C conditions, the rate performance of materials A1 and A2 prepared by the method of the present application is relatively high.

[0110] according to Figure 2 It can be seen that after 150 cycles, the capacity retention rate of the halogen-free quaternary positive electrode material D1 is 82.2%; the capacity retention rate of the sample D2 introduced with LiCl is 84.6%; the capacity retention rates of the chlorine-doped quaternary materials A1 and A2 prepared by the method disclosed in the present invention are 92.0% and 89.0%, respectively.

[0111] According to the above data, the halogen-doped quaternary positive electrode material prepared by the method of the present invention has uniform mixing of the elements, and when used as a positive electrode material for a lithium-ion battery, it has higher rate performance and better cycle performance.

[0112] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments; within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0113] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0114] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a halogen-doped quaternary positive electrode material, characterized in that: The method comprises the following steps: S1, performing a first solid phase mixing of nickel hydroxide, an aluminum source and a manganese source to obtain a first solid material; S2, performing a second solid phase mixing of the first solid material and a cobalt source, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material; S3, performing a third solid phase mixing of the second solid material and a lithium source, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere; At least one of the cobalt source, the manganese source, and the aluminum source contains a halogen.

2. The method according to claim 1, wherein: The aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate, aluminum acetate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide; The manganese source includes one or more of manganese hydroxide, manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate, manganese acetate, manganese fluoride, manganese chloride, manganese bromide and manganese iodide; The cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt fluoride, cobalt chloride, cobalt bromide and cobalt iodide; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

3. The method according to claim 1, wherein: The first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling, and the time is 1-5 hours respectively.

4. The method according to claim 1, wherein: In step S2, the first heat treatment method includes calcination, and the conditions of the first heat treatment include: time of 2-8h and temperature of 400-900°C.

5. The method according to claim 1, wherein: In step S3, the second heat treatment method includes roasting, and the conditions of the second heat treatment include: time is 10-20h, and temperature is 600-850°C.

6. The method according to claim 1, wherein: The average particle size of the nickel hydroxide is 5-15 μm.

7. The method according to claim 1, wherein: The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere.

8. A halogen-doped quaternary positive electrode material prepared by the method according to any one of claims 1 to 7.

9. A halogen-doped quaternary positive electrode material, characterized in that: The quaternary cathode material includes particles with the chemical formula LiNi 1-x-y-z Co x Mn y Al z O 2-0.5p X p , where 0.6 ≤ 1 - x - y - z < 1, 0 < x ≤ 0.15, 0 < y ≤ 0.15, 0 < z ≤ 0.1, 0 < p ≤ 0.1, and X is one or more of F, Cl, Br, and I.

10. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the halogen-doped quaternary positive electrode material according to claim 8 or 9.

Citation Information

Patent Citations

  • Lithium ion quaternary positive electrode material, preparation method thereof and lithium ion battery

    CN113488642A

  • Niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material, preparation method thereof and lithium ion battery containing niobium-doped nickel-cobalt-manganese lithium aluminate quaternary material

    CN116072858A

  • Negative electroactive materials and methods of forming the same

    US20230102190A1